2023
DOI: 10.3390/cimb45040224
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping and QTL Analysis of Fruit Traits in Melon (Cucumis melo L.)

Abstract: Melon (Cucumis melo L.) is an important horticultural cash crop and its quality traits directly affect consumer choice and market price. These traits are controlled by genetic as well as environmental factors. In this study, a quantitative trait locus (QTL) mapping strategy was used to identify the potential genetic loci controlling quality traits of melons (i.e., exocarp and pericarp firmness and soluble solid content) based on newly derived whole-genome single nucleotide polymorphism-based cleaved amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This strategy was also suggested by Zhang et al (2010), to increase acidity in the pulp of melon fruit. It should also be noted that efforts have been made to obtain melon cultivars with more acidic and/or sweet fruit, especially by research groups in Israel (BURGER et al, 2003;COHEN et al, 2014;GUR et al, 2017) and Asia (ZHANG et al, 2010;ZHANG et al, 2016;ZHU et al, 2013;KIM, 2006). With greater demand from the consumer market, and a tendency towards diversifying the types of melon fruit, the development of more-acidic melon cultivars, maintaining the current levels of sugars, is promising, as it would result in fruit with more-fl avourful pulp, which is determined by the ratio of soluble solids to titratable acidity.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy was also suggested by Zhang et al (2010), to increase acidity in the pulp of melon fruit. It should also be noted that efforts have been made to obtain melon cultivars with more acidic and/or sweet fruit, especially by research groups in Israel (BURGER et al, 2003;COHEN et al, 2014;GUR et al, 2017) and Asia (ZHANG et al, 2010;ZHANG et al, 2016;ZHU et al, 2013;KIM, 2006). With greater demand from the consumer market, and a tendency towards diversifying the types of melon fruit, the development of more-acidic melon cultivars, maintaining the current levels of sugars, is promising, as it would result in fruit with more-fl avourful pulp, which is determined by the ratio of soluble solids to titratable acidity.…”
Section: Resultsmentioning
confidence: 99%
“…Candidate genes have been proposed for ethyl 3-(methylthio) propanoate and benzaldehyde biosynthesis (Mayobre et al 2021). A set of Near-Isogenic Lines (NILs) containing overlapping introgressions from the Korean accession 'SC' showed climacteric ripening QTL, ETHQB3.5, were also involved in VOCs biosynthesis (e.g., 3-methylbutyl acetate, benzyl acetate, 2-methylbutan-1-ol, 2-methylpropyl acetate, and 1-methylsulfanylbutan-1-one) (Zhao et al 2023).…”
Section: Fruit Traitmentioning
confidence: 99%
“…When used in conjunction with conventional selection methods, MAS has been confirmed to be an effective tool for selecting plants with desirable traits. Several genomic regions and candidate genes associated with essential horticultural traits, such as fruit quality attributes, ripening behavior, and carotene content, have been identified using QTL mapping analysis in molecular breeding programs [12][13][14][15][16]. Genetic linkage maps and molecular markers for the QTLs of horticultural traits in melons identified in previous studies are briefly reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%